Bioactivities of the thai medicinal and edible plants C. cajan, M. citrifolia and O. americanum - Monika Mueller (2018)
© 2015, International Journal of Pharmacy and Pharmaceutical Science. All rights reserved. Objective: Inflammation and oxidative stress are closely related and play a role in various diseases. If an infectious component plays a role, an antibacterial effect is of advantage. Thus, natural remedies which combine different bioactivities have a broader range of application. Methods: Here we elucidate the anti-inflammatory, antioxidant and antibacterial effects of three edible and traditionally used Thai plants including leaves of Cajanus cajan, Morinda citrifolia and Ocimum americanum. Results: The extracts exerted significant anti-inflammatory activity in lipopolysaccharide (LPS)-stimulated macrophages. C. cajan extract shows a broad spectrum of antibacterial activity against Gram positive and negative, aerobic and anaerobic bacteria, whereas M. citrifolia and O. americanum possess antibacterial activity only against anaerobic bacteria. Extracts of all three plants showed significant antioxidant effects Conclusion: The three plants are potential herbal remedies or supplements for functional food for the treatment and prevention of inflammation, oxidative imbalance, and bacterial infections or associated diseases.